Having trouble with proving it, Y''-Y'-12Y=0; e^-3x, e^4x, (-inf, inf)
so it says in the answers that cause W(e^-3x,e^4x)=e^7x obviously it can't equal 0 but how do you come up with the e^7x? I am missing something somewhere.
Thanks
Having trouble with proving it, Y''-Y'-12Y=0; e^-3x, e^4x, (-inf, inf)
so it says in the answers that cause W(e^-3x,e^4x)=e^7x obviously it can't equal 0 but how do you come up with the e^7x? I am missing something somewhere.
Thanks
when solving using the quadratic formula and you have m'' and m' so that you get Y=C(e^(m"x))+K(e^(m'x)) where C,K are arbiturary constants does order matter? Like can it be written Y=K(e^(m'x))+C(e^(m"x))